2019
DOI: 10.3389/fneur.2019.01047
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Factors Contributing to Parkinson's Disease: A Case-Control Study in the Cypriot Population

Abstract: Introduction: Parkinson's disease (PD) is a neurodegenerative disorder affecting a substantial proportion of the elderly Cypriot population. The objective of this study was to evaluate PD risk variants that have been identified previously in Genome Wide Association Studies (GWAS) and to find environmental factors that are predictors for PD onset in the Cypriot population.Methods: A case-control study was conducted with a total of 235 PD patients and 464 healthy controls of Greek-Cypriot ethnicity. Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Our study further revealed that the use of tobacco products is inversely associated with PD. Our findings are consistent with previous reports, which showed that smoking might be protective against PD [26].…”
Section: Discussionsupporting
confidence: 94%
“…Our study further revealed that the use of tobacco products is inversely associated with PD. Our findings are consistent with previous reports, which showed that smoking might be protective against PD [26].…”
Section: Discussionsupporting
confidence: 94%
“…After a full-text evluation, a total of 21 case-control studies [2,[10][11][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] met the inclusion criteria. Among these studies, 9 studies carried out in America [10,11,17,18,20,21,22,26,28], 9 studies in Europe [2,16,19,23,24,25,27,31,33]and3 studies in Asia [29,30,32]. Eight studies were published before 2005 [10,11,19,22,25,31,32,33]and 13 afterwards…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among these studies, 9 studies carried out in America [10,11,17,18,20,21,22,26,28], 9 studies in Europe [2,16,19,23,24,25,27,31,33]and3 studies in Asia [29,30,32]. Eight studies were published before 2005 [10,11,19,22,25,31,32,33]and 13 afterwards [2,16,17,18,20,21,23,24,26,27,28,29,30].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial evidence indicating that PD in elderly individuals may have its origin in exposure to environmental factors such as well water, pesticides, and ionizing radiation during early life, including young adulthood. [5][6][7][8][9] Our study population stays in Iğdır, an agricultural region of eastern Turkey, where pesticides have been used since 1960. Interestingly, PD prevalence in Iğdir is higher than that in other regions of Turkey.…”
mentioning
confidence: 99%